Juventudes e corpo: um olhar antropológico sobre o ensino da dança na rede estadual de Goiânia - Castilho, Grazielle de (2025)
This dissertation aims to articulate dance and anthropology to understand the production of youth through dance teaching in the school environment and how social markers permeate these processes. To this end, I chose ethnographic research with participant observation of a group of young people aged 13 to 16 in elementary school II and the dance teacher of a state school located in the Jardim América district of the city of Goiânia. Thus, I seek to carry out an anthropological reading of the body, youth and dance. And to analyze in the field the practices and meanings of dance teaching and the way in which social markers permeate the course of young people's lives. In this scenario, this writing will occur through research with an ethnographic method that will allow a description in which it will take into account my experiences and those of young people in the processes and interactions. In view of this, my main objective is to analyze the practices and meanings of dance teaching in the field; identify how social markers influence the experiences of young people and suggest paths for dance practices that demonstrate respect and plurality